A family of global classical solutions to 3D incompressible nematic liquid crystal flows. (December 2015) - Shao, Shuguang; Ge, Yuli; Zhang, Yuwei
Abstract: In this paper we construct a family of finite energy smooth solutions to the three-dimensional incompressible nematic liquid crystal flows. We achieve this by choosing the steady state Beltrami flows which have infinite energies as the initial data and using a special cut-off technique.